Dissent, discourse, and democracy whistleblowers as sites of political contestation - Guitar, Joshua, 1986- (Lexington Books, 2021)
"Dissent, Discourse, and Democracy theorizes abstruction analysis as a method of critical rhetorical inquiry and employs it in the evaluation of prominent government whistleblower discourses. Guitar reveals how whistleblowing, a quintessential tool of dissent within democracy, has been systematically constrained within the public forum and weaponized for statist interests"--